Exploring the functional and immune landscape of E-β thalassemia patients through RNA sequencing of peripheral blood mononuclear cells - Nibedita Mitra; Prosanto Chowdhury; Anupam Basu (Heliyon)
Thalassemia is a hematological disorder caused by mutations in the hemoglobin gene, often necessitating regular blood transfusions. These frequent transfusions exert continuous pressure on patients' immune systems. Despite extensive research on the hematological aspects of thalassemia, few studies have explored the immune status of these patients.In this study, we investigated the immune profiles of thalassemia patients using peripheral blood mononuclear cells (PBMCs). We examined the transcriptomes of PBMCs from five severe thalassemia patients, five non-severe patients, and five healthy volunteers. After isolating PBMCs, we extracted total RNA and performed RNA sequencing using the NOVASEQ 6000 platform. We analyzed the raw counts to observe differential gene expression between thalassemia patients and healthy controls, as well as between severe and non-severe patients. Additionally, we conducted gene set enrichment analysis (GSEA) to explore underlying immune conditions.The gene expression profile, along with GSEA, revealed a marked decrease in MHC-II-mediated antigen presentation. Notably, we identified, for the first time, the activation of reactive oxygen species (ROS) through NK cell-mediated eosinophil chemotaxis, suggesting a link to disease severity. Severe thalassemia patients also exhibited higher expression of pro-inflammatory cytokines. Furthermore, transcriptome analysis showed increased expression of the ABO gene in severe thalassemia patients, which may contribute to heightened immune reactions and an increased need for blood transfusions. Deconvolution of the RNA-seq data revealed lower abundances of CD4 T cells and monocytes in thalassemia patients.Thus, immune-modulating drugs could be explored as alternative therapeutic options for the management of thalassemia.